2021
DOI: 10.3390/ncrna7030044
|View full text |Cite
|
Sign up to set email alerts
|

From Yeast to Mammals, the Nonsense-Mediated mRNA Decay as a Master Regulator of Long Non-Coding RNAs Functional Trajectory

Abstract: The Nonsense-Mediated mRNA Decay (NMD) has been classically viewed as a translation-dependent RNA surveillance pathway degrading aberrant mRNAs containing premature stop codons. However, it is now clear that mRNA quality control represents only one face of the multiple functions of NMD. Indeed, NMD also regulates the physiological expression of normal mRNAs, and more surprisingly, of long non-coding (lnc)RNAs. Here, we review the different mechanisms of NMD activation in yeast and mammals, and we discuss the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 179 publications
(239 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, in our data there are 60 interactions involving 83 proteins encoded by LINC genes (long intergenic non-protein coding RNA), 67 of which are annotated as “uncertain”. A fraction of this dataset is expected to be updated into fully characterized LINC-encoded microproteins [ 44 ]. In the most recent protein evidence update of NeXtProt [ 20 ], 1, 12 and 8 of the 83 uncertain protein products of LINC genes were, respectively, upgraded to PE1, PE2 and PE4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our data there are 60 interactions involving 83 proteins encoded by LINC genes (long intergenic non-protein coding RNA), 67 of which are annotated as “uncertain”. A fraction of this dataset is expected to be updated into fully characterized LINC-encoded microproteins [ 44 ]. In the most recent protein evidence update of NeXtProt [ 20 ], 1, 12 and 8 of the 83 uncertain protein products of LINC genes were, respectively, upgraded to PE1, PE2 and PE4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…NMD is a well-conserved cytoplasmic mRNA quality control mechanism that has been found in species across the eukaryotic kingdom [45,46]. Although it was originally discovered to target PTC-containing transcripts, later research revealed that a large portion of normal, error-free mRNAs and some non-coding RNA species are also substrates of this pathway (reviewed in [56]). Thus, NMD functions beyond quality control and is now considered as a more general mechanism for post-transcriptional gene regulation [57,58].…”
Section: Further Surveillance In the Cytoplasm-detection Of Errors Via Nonsense-mediated Decaymentioning
confidence: 99%
“…In addition, transcriptome-wide analysis of yeast RNPs has revealed that Gbp2 is also strongly associated with small nucleolar RNAs and long noncoding (lnc) RNAs [117]. Subsequent reports demonstrated that lncRNAs engaged in translation could be targeted to NMD, and this is functionally significant for the regulation of gene expression [56,68,150,151]. Recent reports have further implicated a regulatory interplay between human SR proteins, microRNAs, and lncRNAs underlying oncogenic or other health effects [152][153][154][155][156].…”
Section: Closing Remarksmentioning
confidence: 99%
“…They make an intimate part of mechanisms controlling cell/tissue homeostasis as well as various diseases including cancers (Rinn & Chang, 2012) now nicely reported in the CLC2 lncRNA database (Vancura et al., 2021). Although lncRNAs were initially defined as noncoding, several contain open reading frames (ORFs) that are translated into functional peptides and subjected to translation‐dependent decay (Andjus et al., 2021; Chen, 2020). Among lncRNAs, circRNAs are circular molecules with a covalently closed loop structure lacking 5′cap and 3′polyadenylated tail, formed through noncanonical splicing (Kristensen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%